Autoantibodies in patients with interleukin 12 receptor beta 1 deficiency. Issue 7 (10th July 2019) - Ronca, Vincenzo; Chen, Qu Bo; Lygoura, Vasiliky; Ben‐Mustapha, Imen; Shums, Zakera; Trifa, Mehdi; Carbone, Marco; Mancuso, Clara; Milani, Chiara; Bernuzzi, Francesca; Ma, Xiong; Agrebi, Nourhen; et al.
Abstract : Objective: Interleukin 12 receptor beta 1 (IL‐12Rβ1) deficiency is a primary immunodeficiency that exposes affected individuals to an augmented risk of intracellular pathogen‐mediated infections. The paradoxical presence of autoimmune manifestations in immune‐deficient patients has been recognized, but the basis of this phenomenon is unclear, with the role of frequent infections being a possible trigger to break tolerance. Our study aimed to analyze extensively a profile of autoantibodies in a clinically well‐defined case series of patients with IL‐12Rβ1 deficiency. Methods: Eight patients with IL‐12Rβ1 deficiency referred to Children's Medical Center in Tunis, Tunisia, during 1995‐2012 were enrolled in the study. Sixteen age‐ and gender‐matched blood donors served as controls. Serum, liver‐related autoantibodies immunoglobulin (Ig)G, IgM, IgA were tested by ELISA and by standard indirect immunofluorescence on Hep‐2 cells. Results: We found a significant prevalence of liver autoantibodies in the study group. Regarding primary biliary cholangitis (PBC), two of eight patients were positive for MIT3 autoantibodies, both confirmed by immunofluorescence, and one patient was positive for PBC‐specific antinuclear antibodies, sp100. Moreover, two patients had significantly increased gamma‐glutamyltransferase levels and one had IgM levels twice the upper limit of normal. Intriguingly two patients were positive for anti‐actin antibodies; a typical feature of autoimmune hepatitis type 1, along with a significant increase in IgG levels. Conclusions: This is the first report of a serological analysis in patients with an IL‐12Rβ1 deficiency. Despite the difficulty in interpreting the role of the IL‐12, the evidence of liver‐specific autoantibodies confirms the importance its signal in liver autoimmunity.